Understanding the Freedom of Religion in a Religious Industry: Kosher Slaughter (Shechita) and Animal Welfare - Silver, Joel (Victoria University of Wellington Law Review, 2011)
The legality of ritual slaughter rests upon both law and merits. On the one hand, the international freedom of religion requires that communities can obtain meat of a suitable standard, and on the other, current scientific literature indicates that any distinct risks to animal welfare are manageable. Despite this, ritual slaughter remains controversial, particularly Jewish kosher slaughter (Shechita), for which electrical pre-stunning before throat-cutting – arguably the sine qua non of welfare risk management – is incompatible. Through a mixture of theological, legal, and scientific argument, this paper examines the level of protection Shechita receives as a manifestation of belief, with particular reference to developments in Australia and New Zealand.